Divine justice [compact disc, unabridged] - Baldacci, David (Baldacci, David. Camel Club., 2008)
In this fourth of the Camel Club series, two bullets silence Oliver Stone's foes. Those assassinations set off a manhunt of enormous proportions by some of the highest officials in government. The Camel Club must fend for itself, all the while protecting their elusive leader, Stone, as he avoids capture by the sometimes uninformed Joe Knox, the man in charge of the hunt.